Power mobile academic planner - Costales, Jennifer I.; Lapuz, Jessie Rose C.; Vinluan, Edward R. (2003.)
Nowadays, the need for an efficient scheduling mechanism is essential especially for people involved in various activities. In accordance with this, a scheduler that is fast, easy-to-use and convenient is vital. There are many facilities available in the market for managing schedule. However, these systems have major drawbacks such as limited capabilities, cost issues and incapability to operate in real time. With the advancement of the wireless era, a scheduler that is limited within the confines of a desktop computer is not enough. As the prevalence of communication devices and mobile computing grows, the problem of interoperability also arises. In order to cope with the problem of scheduling and interoperability in mobile devices, PowerMAP was developed. PowerMAP is a mobile academic planner connected to the Easy.NET web server thereby allowing users to send email, post and get deadlines, quizzes, calendar events, and update schedules. Users are notified about their events through alerts sent as text messages or email. PowerMAP was built using J2ME technology, the same technology that provides Java solutions to mobile devices. Aside from that, this application uses SyncML as its synchronization protocol. With SyncML, events and schedules will be consistent, accessible and up to date, no matter where the information is stored, no matter which mobile device is being used. A compact and user-friendly applciation with the combined reliability of Java and the interoperability of SyncML, PowerMAP gives the users a mechanism to organize their schedules anytime, anywhere.
Thesis (B.S. Computer Science)--University of the Philippines, Diliman.
Keywords: Personal communication service systems; Mobile computing -- Programming; Time management -- Computer programs; PowerMAP